Tribological properties and corrosion resistance enhancement of H13 hot work steel by means of CrN/TiN multilayers (2010)
ABSTRACT: Steel AISI H13 is used mainly for fabrication of hardened hot work tools; however life time of this steel is limited by its relatively low wear and corrosion resistance, if it would be exposed to an aggressive environment. It is widely known that the performance of tools and parts that undergo high mechanical load can be enhanced by the use of monolayer hard thin coatings. However, the use of such coatings as corrosion barriers is often unsatisfactory, since the deposition processes usually generate small pores and pinholes, which negatively affect the electrochemical behaviour of the coating/substrate system. On the other hand, if a hard thin film covers a less noble material, such as steel, small anodic areas could be generated and exposed to an aggressive environment a galvanic corrosion would take place. Therefore, it is also necessary to optimize the design of the coating system used in order to achieve the better relationship between mechanical and electrochemical properties for the whole system. The intention of the presented work was to enhance the tribological properties and corrosion resistance of steel AISI H13 through the use of a CrN/TiN multilayer coatings system, which were deposited by using the balanced magnetron sputtering technique.